2010
DOI: 10.1021/ml100306h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AMG 369, a Thiazolo[5,4-b]pyridine Agonist of S1P1 and S1P5

Abstract: The optimization of a series of thiazolopyridine S1P1 agonists with limited activity at the S1P3 receptor is reported. These efforts resulted in the discovery of 1-(3-fluoro-4-(5-(1-phenylcyclopropyl)thiazolo-[5,4-b]pyridin-2-yl)benzyl)azetidine-3-carboxylic acid (5d, AMG 369), a potent dual S1P1/S1P5 agonist with limited activity at S1P3 and no activity at S1P2/S1P4. Dosed orally at 0.1 mg/kg, 5d is shown to reduce blood lymphocyte counts 24 h postdose and delay the onset and reduce the severity of experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 24 publications
1
33
0
2
Order By: Relevance
“…95 AMG 369 acts as a potent S1P 1 and S1P 5 agonist, showing low S1P 3 activity and being inactive towards S1P 2 and S1P 4 . 95 The absence of cardiovascular effects even at concentrations as high as 10 mg/kg of AMG 369 in rats further indicate the correlation of bradycardia with S1P 3 agonism in the rodent model.…”
Section: Structural Diversity Of S1p1 Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…95 AMG 369 acts as a potent S1P 1 and S1P 5 agonist, showing low S1P 3 activity and being inactive towards S1P 2 and S1P 4 . 95 The absence of cardiovascular effects even at concentrations as high as 10 mg/kg of AMG 369 in rats further indicate the correlation of bradycardia with S1P 3 agonism in the rodent model.…”
Section: Structural Diversity Of S1p1 Modulatorsmentioning
confidence: 99%
“…95 AMG 369 acts as a potent S1P 1 and S1P 5 agonist, showing low S1P 3 activity and being inactive towards S1P 2 and S1P 4 . 95 The absence of cardiovascular effects even at concentrations as high as 10 mg/kg of AMG 369 in rats further indicate the correlation of bradycardia with S1P 3 agonism in the rodent model. 82,95 Oral bioavailability was found to range between 34–64% in rat, dog, and non–human primate experiments, and a depletion of PDL counts 24 hrs after oral administration of 0.1 mg/kg led to a significant delay of EAE onset in the rat model.…”
Section: Structural Diversity Of S1p1 Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pursuing novel S1P 3 -R–sparing S1P 1 -R agonists, Amgen concomitantly modified the azetidine carboxylate head-group of AMG369 while keeping its lipophilic tail (Table 7). 40-41 Of note, 3-amino succinamic acids 23a, 23b and α-methyl-α-aminobutyrate (–)- 23c proved exceptionally potent S1P 1 -R agonists with EC 50 ’s in sub-nanomolar range and highly selective against the S1P 3 -R. The selectivity at the S1P 5 -R was not provided even though AMG369 was previously reported to have a nanomolar S1P 5 -R agonist activity. 41 Amongst the explored molecules, 23c showed the best efficacy in reducing PBL counts following oral dosing in rats at 1 mg/kg, and moderate lymphocyte depletion could be observed even at 0.3 mg/kg.…”
Section: S1p1-r Agonistsmentioning
confidence: 99%
“…The 24 h time point was selected for our studies, as it was found to mitigate the effects of dosing on lymphocyte counts. 17 Notably, carbamoylnicotinamide 8 reaches >5-fold higher concentration in plasma than the other compounds tested in Table 1 (64 ng/mL) and is also the only one that effects statistically significant (P < 0.05 vs vehicle by the ANOVA/Dunnett's multiple comparison test) reduction in circulating lymphocytes (POC = À67%). Given their comparable in vitro profiles, it is unclear why compounds 14À16 and 18 do not achieve higher plasma levels and realize statistically significant reduction of peripheral lymphocyte counts (PLCs).…”
Section: 26mentioning
confidence: 92%